2008
DOI: 10.1016/j.cardfail.2007.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Objectively Measured, but Not Self-Reported, Medication Adherence Independently Predicts Event-Free Survival in Patients With Heart Failure

Abstract: Dose-count and dose-day predicted event-free survival. Neither dose-time nor self-reported adherence predicted outcomes. Health care providers should assess specific behaviors related to medication taking rather than a global patient self-assessment of patient adherence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
152
2
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 135 publications
(164 citation statements)
references
References 52 publications
8
152
2
2
Order By: Relevance
“…With patient or family assistance, hospital discharge and other medical records were obtained from identified sources of care outside of the study‐site healthcare systems. We have >20 years of experience collecting these data and have successfully obtained hospitalization data on all rural patients in our current and previous studies 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41. All‐cause mortality data (date and cause of death) were collected for 1 year from baseline by a combination of medical record review, electronic clinical record review, interviews with patients’ healthcare providers and family, and public death record review 30, 31, 40, 41, 42, 43…”
Section: Methodsmentioning
confidence: 99%
“…With patient or family assistance, hospital discharge and other medical records were obtained from identified sources of care outside of the study‐site healthcare systems. We have >20 years of experience collecting these data and have successfully obtained hospitalization data on all rural patients in our current and previous studies 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41. All‐cause mortality data (date and cause of death) were collected for 1 year from baseline by a combination of medical record review, electronic clinical record review, interviews with patients’ healthcare providers and family, and public death record review 30, 31, 40, 41, 42, 43…”
Section: Methodsmentioning
confidence: 99%
“…4 However, the burden of medications in patients with HF is largely unknown. A study of 16 patients with HF found that patients took an average of 11.1 medications daily.…”
Section: Burden Of Medicationsmentioning
confidence: 99%
“…[3][4][5][6][7][8][9][10] Further, previous studies have frequently identified patients with HF using administrative data alone, an approach known to have poor validity in some settings. 11 In addition, the methodology used to assess medication adherence may be unreliable because use of prescription claims data to assess adherence may miss prescriptions that are not charged to the insurance provider, and self-reported adherence assessments have shown poor correlation with electronic-based adherence.…”
mentioning
confidence: 99%
“…Objective measures, including measurement of clinical outcomes, dose counts, pharmacy records, electronic monitoring of medication administration (e.g. the Medication Event Monitoring System, MEMS) and drug concentrations [18][19][20][21], seemingly provide the best measure of a patient's medication-taking behaviour in many contexts [22][23][24][25][26][27]. It is important to recognize that, while objective, most of these measures have drawbacks.…”
Section: Introductionmentioning
confidence: 99%